Family Experiences in Caring for Patients with Hallucinations: A Phenomenological Study at Naimata Regional Mental Health Hospital - Ninef, Violin Irene; Nenobais, Aplonia; Syahrir, Syahrir (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hallucinations are a form of perceptual disturbance commonly experienced by patients with mental disorders, which impact the quality of life for both the patients and the families who care for them. The objective of this study is to deeply explore the experiences of families caring for patients with hallucinations at Naimata Regional Mental Health Hospital. Method: This study employs a qualitative approach with a phenomenological design. The population consists of families who have a family member suffering from a mental disorder involving hallucinations. The sample includes twelve participants, selected using purposive sampling. Data collection was carried out through in-depth interviews guided by a semi-structured interview protocol. The data were presented in the form of thematic narratives and analyzed using thematic analysis, which included the processes of data reduction, data presentation, and conclusion drawing. The research instruments used were the interview guidelines and a voice recording device. Results: The findings of the study indicate that families experience psychological burdens such as stress, fear, and helplessness, as well as social pressure due to societal stigma. Despite these challenges, families continue to play a crucial role in providing emotional, physical, and social support to the patients. Additionally, support from healthcare providers and the surrounding community significantly aids the caregiving process. Conclusion: This study concludes that the experience of families caring for patients with hallucinations is highly complex and requires mental, emotional, and social readiness. Active interventions involving families are necessary to improve the quality of patient care and the well-being of families in facing these challenges.